Trans-grafting plum pox virus resistance from transgenic plum rootstocks to apricot scions - Alburquerque, Nuria; Pérez-Caselles, Cristian; Faize, Lydia; Ilardi, Vincenza; Burgos, Lorenzo (Frontiers in Plant Science, 2023)
Trans-grafting could be a strategy to transfer virus resistance from a transgenic rootstock to a wild type scion. However contradictory results have been obtained in herbaceous and woody plants. This work was intended to determine if the resistance to sharka could be transferred from transgenic plum rootstocks to wild-type apricot scions grafted onto them. To this end, we conducted grafting experiments of wild-type apricots onto plum plants transformed with a construction codifying a hairpin RNA designed to silence the PPV virus and studied if the resistance was transmitted from the rootstock to the scion. Our data support that the RNA-silencing-based PPV resistance can be transmitted from PPV-resistant plum rootstocks to non-transgenic apricot scions and that its efficiency is augmented after successive growth cycles. PPV resistance conferred by the rootstocks was robust, already occurring within the same growing cycle and maintained in successive evaluation cycles. The RNA silencing mechanism reduces the relative accumulation of the virus titer progressively eliminating the virus from the wild type scions grafted on the transgenic resistant PPV plants. There was a preferential accumulation of the 24nt siRNAs in the scions grafted onto resistant rootstocks that was not found in the scions grafted on the susceptible rootstock. This matched with a significantly lower relative accumulation of hpRNA in the resistant rootstocks compared with the susceptible or the tolerant ones.This was coupled with a significant lower quantification of the hpRNA in the resistant than in the susceptible or tolerant rootstocks. Using transgenic rootstocks should mitigate public concerns about transgenes dispersion and eating transgenic food and allow conferring virus resistance to recalcitrant to transformation cultivars or species.